Ionic nanocomposite networks in poly(styrene‐co‐methacrylic acid) copolymers with calcium carbonate. Issue 1 (16th November 2012) - Chevallier, Celine; Ni, Yiping; Vera, Ruben; Becquart, Frederic; Taha, Mohamed
Abstract To create reversible supramolecular ionic networks, ionic cross‐links were formed from acid pendant functions in poly(styrene‐co‐methacrylic acid) copolymers by the addition of calcium carbonate. The random dispersion of acid functions in the polystyrene chain is ensured by NMR analysis. The partial reaction of the calcium carbonate with the carboxylic acids is highlighted by a limewater test. The influence of methacrylic acid and calcium‐carbonate contents on the formation of an ionic network has been studied through solubility tests. Two main effects were obtained: the exfoliation of the unreacted calcium carbonate characterized by TEM is due to ionic interactions at the surface of nanometric particles that form the first level of organization of the calcium carbonate. Another part of the calcium carbonate reacts with carboxylic acid and is detached from particles to form clusters as shown by x‐ray analysis. Finally, by analyzing the dynamic rheological spectrum, the conclusion that the strength of the ionic bonds arises with the calcium content is made. The interest of such an approach with a wide range of observed phenomena in the material is a one‐batch process to make thermoreversible nanocomposite networks. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013